Ecological drivers of taxonomic, functional, and phylogenetic beta diversity of macroinvertebrates in Wei River Basin of northwest China - Li, Jiaxin; Ma, Mengdi; Wang, Luyao; Jin, Yujun; Liu, Yiming; Yin, Xuwang; Liu, Gang; Song, Jinxi (Frontiers in Ecology and Evolution, 2024)
Understanding biodiversity changes, along with its driving factors and mechanisms, is crucial in biogeography and community ecology. Beta diversity is an indicator for discerning the compositional variations among communities and is essential role in fostering a comprehensive understanding of the ecological processes shaping biodiversity distribution patterns. This study quantitatively evaluated the beta diversity of macroinvertebrates in the Wei River Basin, focusing on: (i) contributions of turnover and nestedness to taxonomic, functional, and phylogenetic total beta diversity, (ii) correlations between these beta diversity dimensions, and (iii) the influences of local, climatic, and spatial factors on beta diversity. We analyzed macroinvertebrate data from 51 sampling locations in the Wei River Basin and explored the relationships between different beta diversity dimensions using the Mantel test. Additionally, we assessed the relative influence of local, climatic, and spatial factors on beta diversity through distance-based redundancy analysis and variance partitioning methods. The results indicated that turnover predominantly affects taxonomic and phylogenetic beta diversity, while nestedness mainly drives functional beta diversity. Functional beta diversity was more weakly associated with the other dimensions. Local environmental factors significantly influenced taxonomic and phylogenetic beta diversity, whereas spatial factors had a stronger influence on functional beta diversity. Our findings highlight the need for conservation strategies to integrate taxonomic, functional, and phylogenetic dimensions, transcending traditional species-level approaches.